Neuron-astrocyte metabolic coupling facilitates spinal plasticity and maintenance of inflammatory pain [data] - Marty-Lombardi, Sebastián; Lu, Shiying; Ambroziak, Wojciech; Schrenk-Siemens, Katrin; Wang, Jialin; DePaoli-Roach, Anna A.; Hertle, Anna M.; Wende, Hagen; Tappe-Theodor, Anke; Simonetti, Manuela; Bading, Hilmar; Okun, Jürgen G.; et al. (Universität, 2024)
Long-lasting pain stimuli can trigger maladaptive changes in the spinal cord, reminiscent of plasticity associated with memory formation. Metabolic coupling between astrocytes and neurons has been implicated in neuronal plasticity and memory formation in the CNS, but neither its involvement in pathological pain nor in spinal plasticity has been tested. Here, we report a form of neuroglia signaling involving spinal astrocytic glycogen dynamics triggered by persistent noxious stimulation via upregulation of the Protein Targeting to Glycogen (PTG) in spinal astrocytes. PTG drove glycogen build-up in astrocytes, and blunting glycogen accumulation and turnover by Ptg gene deletion reduced pain-related behaviors and promoted faster recovery by shortening pain maintenance in mice. Furthermore, mechanistic analyses revealed that glycogen dynamics is a critically required process for maintenance of pain by facilitating neuronal plasticity in spinal lamina 1 neurons. In summary, our study describes a previously unappreciated mechanism of astrocyte-neuron metabolic communication through glycogen breakdown in the spinal cord that fuels spinal neuron hyperexcitability. (2024-01-23)
Gesehen am 29.01.2024
Keywords: Forschungsdaten; Datenbank